2020
DOI: 10.1111/jam.14872
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vitro antimicrobial activity of amphotericin B with berberine against dual‐species biofilms of Candida albicans and Staphylococcus aureus

Abstract: Aims Multi‐species biofilms formed by fungi and bacteria are clinically common and confer the commensal micro‐organisms with protection against antimicrobial therapies. Previously, the plant alkaloid berberine was reported to show antimicrobial efficacy to eliminate bacterial and fungal biofilms. In this study, the combination of berberine and amphotericin B, an antifungal agent, was evaluated against dual‐species Candida albicans/Staphylococcus aureus biofilms. Methods and Results Combinatorial treatment by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 42 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…aureus [21]. Some other studies report the inhibitory effect of berberine on developed biofilm, in which biofilm exposed to berberine near MIC for 12–24 h shows a significant decrease in biomass [22, 23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus [21]. Some other studies report the inhibitory effect of berberine on developed biofilm, in which biofilm exposed to berberine near MIC for 12–24 h shows a significant decrease in biomass [22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…A previous investigation reports that at sub-inhibitory concentration, berberine increases the final biofilm biomass of some strains while decreasing it of other strains, suggesting the strain-dependent effect of berberine on biofilm formed by S. aureus [21]. Some other studies report the inhibitory effect of berberine on developed biofilm, in which biofilm exposed to berberine near MIC for 12-24 h shows a significant decrease in biomass [22,23].…”
Section: Berberine Inhibits Biofilm Dispersal At Sub-inhibitory Conce...mentioning
confidence: 90%
“…Eugenol with fluconazole or azithromycin also exhibited enhanced antibiofilm activity against C. albicans-S. mutans biofilm (Jafri et al, 2020). In addition, 2-aminobenzimidazole with curcumin (Tan et al, 2019), berberine and amphotericin B (Gao et al, 2021), anidulafungin and tigecycline (Rogiers et al, 2018), and fluconazole and minocycline (Li et al, 2015) were effective in deterring C. albicans-S. aureus biofilm. Interestingly, some antifungal agents are repurposed to treat C. albicans involved cross-kingdom biofilms.…”
Section: Synthetic Antibiofilm Productsmentioning
confidence: 98%
“…mutans biofilm (Jafri et al ., 2020). In addition, 2‐aminobenzimidazole with curcumin (Tan et al ., 2019), berberine and amphotericin B (Gao et al ., 2021), anidulafungin and tigecycline (Rogiers et al ., 2018), and fluconazole and minocycline (Li et al ., 2015) were effective in deterring C . albicans–S .…”
Section: Therapeutic Approaches For Candida–bacterial Biofilm‐associa...mentioning
confidence: 99%
“…Berberine has been reported to have antibacterial efficacy in eliminating bacterial and fungal biofilms. As such, berberine exerted synergistic effects on inhibiting Candida albicans / S. aureus dual strain biofilms in combination with amphotericin B, an efficient antibiotic that utilized for the treatment of fungal infections in clinic ( Gao et al, 2021 ). A study by Ning et al demonstrated that berberine inhibited biofilm formation via downregulation of the expression of the QS regulatory gene agrA in a concentration-dependent manner in S. aureus ( Ning et al, 2022 ).…”
Section: Quorum Sensingmentioning
confidence: 99%